NOVEL GADIS PANTAI KARYA PRAMOEDYA ANANTA TOER: ANALISIS BERDASARKAN KONSEP ANDROGINI - . Supriyadi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2005)
Feminism firstly developed in France, but recently it has spread all over the world covering all aspects of life. particularly in the relations between men and women. Women feel that they have not had the same rights as men. A branch of feminism which attempts to abridge the relations is androgyny, with a concept of harmony where men and women should work together to reach social welfare. The concept is interesting particularly when applied in literary works written by male writers. Feminism then is also seen on men perspective. Gadis Pantai is one of Indonesian novels written by Pramoedya Anantya Toer which discusses feminism. The story is about a girl, whose name is Gadis Pantai, living in Rembang in the beginning of the twentieth century. She is the symbol of ordinary or laymen. She suffered when Bendoro, the symbol of noblemen, took her as his wife. The story is about the struggle between the two symbols